Temporary trade barrier implementation and market power: evidence from Latin American economies - Kenney, Samuel (Kansas State University, 2016)
This paper examines temporary trade barrier (TTB) implementation by 13 Latin American economies on a bilateral basis from 2000-2009 considering market power and import shocks. Additionally, we augment our analysis by including the effect of the presence or absence of tariff water on TTB implementation. We find evidence that market power and tariff water play an integral role in TTB implementation while import shocks do not. Using a probit model we estimate that a one standard deviation increase in market power and the absence of tariff water indicator increase the probability that a country imposes an antidumping tariff by 71 and 20 percent respectively, evaluated at their means. Interestingly, we do not find that import shocks have a significant impact on TTB implementation.
Keywords: Temporary trade barriers; Developing economies; Tariff water; Market power; Latin American economies; Antidumping